Implementation versus planmaking the example of List Q and the depressed areas, 1922-39 - Ward, Stephen V. (1986)
This article examines the dichotomy between implementation and planmaking, within a context of some of the explanatory frameworks currently being developed in implementation theory. The distinction is illustrated with reference to the gap between ambitious planning intentions generated locally in the interwar depressed areas of England and Wales, and implying high public investment, and the centrally‐controlled procedures restraining loan‐based public investment in these areas. A detailed investigation is undertaken of the emergence, evolution, and impact of the secret loan sanction blacklists developed by the Ministry of Health in 1922 and known from 1925 as List Q. This highlights how, following the financial orthodoxy broadly defined by the Treasury, the most depressed areas were harshly and consistently discriminated against by this detailed code. The major challenge to this strategy, mounted by the Liberals between 1929 and 1931, is examined, showing how the Ministry of Health resisted any attempt to link town and country planning with a Keynesian‐type public works policy. The failure of the later Special Areas initiatives to achieve any integration with planning intentions is also examined. The overall emphasis is on the role of larger structural forces, in particular the interwar dominance of finance capital, creating a presumption of public expenditure restraint, in contrast to the more idealistic, progressive but ultimately weaker forces which were manifest in planning intentions.